2008
DOI: 10.1504/ijmic.2008.020996
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear estimation is easy

Abstract: Non-linear state estimation and some related topics, like parametric estimation, fault diagnosis, and perturbation attenuation, are tackled here via a new methodology in numerical differentiation. The corresponding basic system theoretic definitions and properties are presented within the framework of differential algebra, which permits to handle system variables and their derivatives of any order. Several academic examples and their computer simulations, with on-line estimations, are illustrating our viewpoin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
187
0
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(197 citation statements)
references
References 78 publications
1
187
0
9
Order By: Relevance
“…This is classically used for parametric estimation [15] and fault diagnosis and fault tolerant control in noisy environment [9] since many years. More recently, this approach is used for marginal applications such as the curvature extrema detection [16].…”
Section: A Existing Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…This is classically used for parametric estimation [15] and fault diagnosis and fault tolerant control in noisy environment [9] since many years. More recently, this approach is used for marginal applications such as the curvature extrema detection [16].…”
Section: A Existing Approachmentioning
confidence: 99%
“…The third sensor is classically scanning horizontally to the ground in order to detect other obstacles. The other contribution of this paper is an original distance-based approach for algebraic derivative calculation based on [9] and adapted to laser sensor constraint. This work has been developed in the framework of the Personal Intelligent City Accessible Vehicle (PICAV) project.…”
Section: Introductionmentioning
confidence: 99%
“…R. Kalman developed an observability theory for linear stationary systems [110,112] [95], and many other researchers. More recently, M. Fliess has showed that the concept of identifiability is strongly connected with the notion of observability [52,67].…”
Section: Nonlinear Observability 311 Definitionsmentioning
confidence: 99%
“…Moreover, for stability reasons, we chose to employ exponentially stable dynamics instead of constant dynamics. It is shown that the proposed approach is realisable thanks to the finite time differentiator as, for example, the one proposed in [6,7] (but for these methods, the delay appears due to the data acquisition frame) or High Order Sliding Mode (HOSM) [18,9].…”
Section: Introductionmentioning
confidence: 99%